Analyzing the influence of microstructured surfaces on the lactic acid production of Lactobacillus delbrueckii lactis in a flow‐through cell system. Issue 8 (22nd June 2017) - Schlegel, Christin; Chodorski, Jonas; Huster, Manuel; Davoudi, Neda; Huttenlochner, Katharina; Bohley, Martin; Reichenbach, Ingo; Buhl, Sebastian; Breuninger, Paul; Müller‐Renno, Christine; Ziegler, Christiane; Aurich, Jan; et al.
Abstract : Microorganisms growing in biofilms might be possible biocatalysts for future biotechnological production processes. Attached to a surface and embedded in an extracellular polymeric matrix, they create their preferred environment and form robust cultures for continuous systems. With the objective of implementing highly efficient processes, productive biofilms need to be understood comprehensively. In this study, the influence of microstructured metallic surfaces on biofilm productivity was researched. To conduct this study, titanium and stainless steel sheets were polished, micromilled, as well as coated with particles. Subsequently, the metal sheets were exposed to the lactic acid producing Lactobacillus delbrueckii subsp. lactis under laminar and homogeneous flow conditions in a custom‐built flow cell. A proof‐of‐concept showed that biofilm formation in the system only occurred on the designated substratum. Following a 24‐h batch cultivation for primary biofilm development, the culture was continuously provided with glucose containing medium. As different experimental series have indicated, the process resulted to be stable for up to eleven days. Primary metabolite productivity averaged around 6–7 g/(L h). Interestingly, the productivity was shown to be affected neither by the type of metal, nor by the applied microstructures. Nevertheless, a higher dry biomass weight determined on micro‐milled substratum indicates a complementary differentiation of biofilm components in future experiments.